INOVASI SISTEM PEMBELAJARAN PADA MASA PANDEMI COVID-19 (SUATU STUDI DESKRIPTIF KUALITATIF DI SMAN 1 EMPANG) - Kurnia, Aka (Jurnal TAMBORA, 2021)
This study aims to meet the needs of an effective and learning systemefficient amid the Covid-19 pandemic. As is known, Coronavirus Disease 2019or Covid-19 is a new type of virus that disrupts the respiratory system,acute pneumonia, causing death. There is concern over the sizethe risk that this creates affects the education sector, namely bythe presence of digital technology-based educational innovations, which replace all formsactivities at school are carried out online (online). Although aiming tofulfill and facilitate the learning process from home, precisely in its applicationstill raises several problems, particularly the ineffectiveness and efficiency of activitieslearning. This study uses a descriptive approachqualitative, where what is collected is in the form of opinions, information not numbers, conceptsand information in the form of description to describe andinterpret an object as it is. The results showed that,one of the effects of the Covid-19 pandemic on the education sector at SMAN 1 Empangare taken several policies in the form of disabling activities at school andapply online learning (online) via Whatsapp, Zoom,Cloud Meeting, and Short Message Service (SMS). If needed, learn toocan be done offline, one of which is that the teacher comes to students directly toprovide motivation to learn to students. However, this has implications forLess effective and efficient learning systems due to insufficient time andalso the amount of costs incurred, so that the policy is still not optimalimplemented. Based on several learning methods used at the timeThe Covid-19 pandemic resulted in the most effective learning methodsis to use the online method through Zoom media and Cloud Meeting.So it can be concluded that this method is an effective method and canimplemented at SMAN 1 Empang during the pandemic.